Pengaruh Millieu Therapy Metode Kreasi Seni Membuat Gelang terhadap Penurunan Kesepian (Loneliness) Lansia - AH Yusuf; Iqlima Dwi Kurnia; Manis Aero Dwi Noerviana (Media Karya Kesehatan, 2018)
Loneliness is a feelings of isolation where people felling lonely. All the elderly certainly desire to prosper in his old age but the fact isn’t all the elderly can reach it due to various reasons such as poverty, currently didn’t have offspring or family who can care for the elderly and the inability of the family in providing care to the elderly, so many elderly people become homeless. In This results used pre-experimental one-group pre-post test design. The population in this research is elderly with amount 76 people. Sample was 12 people taken by purposive sampling technique. Collected data conducted by using a questionnaire and analyzed used the Wilcoxon Signed Rank Test with significance α = 0.05. The results of research concluded that millieu therapy methods the creation of art made bracelet could be decreased loneliness of life of the elderly it can stimulate the cognitive, affective, psychomotor, sosio-emotional and self-esteem. Further research is expected to use control groups and researching other factors that influence loneliness the elderly. Researcher can use millieu therapy in supporting and helping the elderly yo live a best quality.